2021
DOI: 10.1055/a-1481-8683
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights into the Steroidal Module of the Athlete Biological Passport

Abstract: For decades, the class of anabolic androgenic steroids has represented the most frequently detected doping agents in athletes’ urine samples. Roughly 50% of all adverse analytical findings per year can be attributed to anabolic androgenic steroids, of which about 2/3 are synthetic exogenous steroids, where a qualitative analytical approach is sufficient for routine doping controls. For the remaining 1/3 of findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…The isotope ratio mass spectrometry (IRMS) test is currently performed in case of suspicious variations of a steroid profile to confirm the non-endogenous origin of steroids ( 27 ). However, detecting abnormal isotopic values in steroid profile not identified as suspicious by the current criteria of the steroidal module of the ABP, longitudinal IRMS has shown a better sensitivity ( 28 ) and a lower individual variability ( 29 , 30 ) in comparison to the traditional approach, based on the concentrations and concentration ratios of the steroid markers.…”
Section: Development Of Current Modulesmentioning
confidence: 99%
“…The isotope ratio mass spectrometry (IRMS) test is currently performed in case of suspicious variations of a steroid profile to confirm the non-endogenous origin of steroids ( 27 ). However, detecting abnormal isotopic values in steroid profile not identified as suspicious by the current criteria of the steroidal module of the ABP, longitudinal IRMS has shown a better sensitivity ( 28 ) and a lower individual variability ( 29 , 30 ) in comparison to the traditional approach, based on the concentrations and concentration ratios of the steroid markers.…”
Section: Development Of Current Modulesmentioning
confidence: 99%
“…This approach is very sensitive to detect doping with pseudo‐endogenous steroids, 6 but the interpretation of results is not always obvious. There are many confounding factors, like ethanol consumption or microbial degradation of urinary steroids, which can influence the steroid profile and eventually hinder the detection of steroid doping in urine 7,8 . Furthermore, the most prominent marker, T/E ratio, may be compromised for sensitivity in population with a deletion polymorphism of the UGT2B17 enzyme, which plays a major role in metabolic fate, more specifically in glucuronide conjugation of T and E 9 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many confounding factors, like ethanol consumption or microbial degradation of urinary steroids, which can influence the steroid profile and eventually hinder the detection of steroid doping in urine. 7,8 Furthermore, the most prominent marker, T/E ratio, may be compromised for sensitivity in population with a deletion polymorphism of the UGT2B17 enzyme, which plays a major role in metabolic fate, more specifically in glucuronide conjugation of T and E. 9 Additionally, the analysis of female samples presents technical issues, as concentrations of endogenous steroids can be below the limit of detection (LOD) or quantification (LOQ) of routine methods. It was also shown that the concentration of E in urine fluctuates over the phases of a menstrual cycle 10 and therefore can decrease the detection capacity of the T/E and 5αAdiol/E ratios.…”
mentioning
confidence: 99%
“…1,2 In order to detect AAS abuse, by xenobiotics similar to endogenous AAS in particular, the World Anti-Doping Agency (WADA) implemented in 2014 the steroidal module of the Athlete Biological Passport (ABP), which longitudinally monitors a number of testosterone-related substances in urine. 3,4 The ABP is an adaptive model, which tracks a number of parameters to detect deviations from a normal physiological condition of an individual. Based on population means and previous individual samples, the model computes upper and lower thresholds and may signal suspicious alterations in case of values outside those calculated limits.…”
Section: Introductionmentioning
confidence: 99%